A multi-version document storage strategy based on chord in large-scale real time collaborative environments. (2017) - Gao, Liping; Zhang, Yuben; Gao, Lili; Chen, Qingkui
In the research field of CSCW, the issue of data management is given little attention compared with other issues. Previous studies mainly focus on how to produce multiple versions. As for the large-scale real time collaborative environment, new storage strategy must be devised because: 1) There are many versions due to the multiple conflict operations, which should be saved to reflect the different intentions of the workers; 2) The new-comer may want to retrieve some old versions to catch up with the work process of the team. The paper devises a multi-version document storage model according to the characteristics of the large-scale real time collaborative environment. This strategy makes full use of the participating sites as the expandable storage resources, based on chord ring as the underlying storage structure and integrates the two storage modes: full storage and incremental storage. Besides, this strategy supports the dynamic change of the chord structure. The strategy realises the document access flexibility and reliability in large-scale collaborative environment, and ensures the storage load balancing between storage nodes. The storage schema is realised in the Co-AutoCAD system and experiments analysis is given to show the effectiveness of the schema.